2016
DOI: 10.15653/tpg-150581
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between uterine biopsy score, endometrial infection and inflammation in the mare

Abstract: Degenerative endometrial changes can predispose to uterine infection and inflammation. Our study shows that mares with endometrial score I are less predisposed to infection than mares with category IIA, IIB and III. Endometrial biopsy is a reliable diagnostic tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(32 reference statements)
1
0
0
Order By: Relevance
“…They were finally diagnosed with endometritis due to a history of infertility, cytologic results related to inflammation as well as a positive bacterial culture result in one of two jennies. Similar results have also been reported that some mares with a biopsy score I have >5% PMN in cytology indicating the presence of mild inflammation of endometrium (Buczkowska et al, 2016). Endometrial cytology is usually used for the evaluation of inflammation by the presence of PMNs.…”
Section: Discussionsupporting
confidence: 84%
“…They were finally diagnosed with endometritis due to a history of infertility, cytologic results related to inflammation as well as a positive bacterial culture result in one of two jennies. Similar results have also been reported that some mares with a biopsy score I have >5% PMN in cytology indicating the presence of mild inflammation of endometrium (Buczkowska et al, 2016). Endometrial cytology is usually used for the evaluation of inflammation by the presence of PMNs.…”
Section: Discussionsupporting
confidence: 84%